Characteristics of the Indonesian Pilgrims Mortality due to Cardiovascular Disease - Sakti, Ali; Alwi, Idrus; Muhadi, Muhadi; Shatri, Hamzah (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. Cardiovascular disease is one of the health problems in Indonesian pilgrims and has become the main cause of death for pilgrims in the past 3 years. Most of them are considered high risk for cardiovascular disease. Some of those risk factors are predicted to have strong association with the pilgrims mortality rate. This study is meant to seek for risk factor associated with the pilgrims mortality rate. Methods. Observational study method of the Indonesian pilgrims in 2017 was conducted to assess the characteristics of Indonesian pilgrims who follow the hajj in 2017 as well as the characteristics of pilgrims who died from cardiovascular disease. Result. The proportion of mortality from cardiovascular disease was 49.2% of all deaths in the Indonesian hajj pilgrims in 2017. Generally, pilgrims are in the category of high risk. Pilgrims who died from cardiovascular disease are mostly aged over 60 years (76.7%) with cardiovascular risk factors including hypertension (53.4%) and obesity (37.3%), and pilgrims with the final wave departure time (53%). Conclusios. The proportion of deaths from cardiovascular disease in the Indonesian pilgrims in 2017 is 49.2%. The characteristics of pilgrims who died with the cause of cardiovascular disease are generally age more than 60 years, pilgrims with hypertension, obesity, and final departure time.